Answer:
3.4
Step-by-step explanation:
Let the original price of the bag be = P, the selling price =2.89 after a 15% discount,
Then, Selling price= Original price- Discount on original price
![2.89=P-P(0.15)](https://tex.z-dn.net/?f=2.89%3DP-P%280.15%29)
![2.89=P(1-0.15)](https://tex.z-dn.net/?f=2.89%3DP%281-0.15%29)
![2.89=0.85P](https://tex.z-dn.net/?f=2.89%3D0.85P)
![P=\frac{2.89}{0.85}](https://tex.z-dn.net/?f=P%3D%5Cfrac%7B2.89%7D%7B0.85%7D)
![P=3.4](https://tex.z-dn.net/?f=P%3D3.4)
Thus, the original price was 3.4.
Answer:
100
Step-by-step explanation: its the same thing but in a different form
Distribute 1/2 to <span>(n – 4):
</span>
![\frac{1}{2} \times n = \frac{1}{2}n](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B2%7D%20%5Ctimes%20n%20%3D%20%5Cfrac%7B1%7D%7B2%7Dn)
![\frac{1}{2} \times -4 = -2](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B2%7D%20%5Ctimes%20-4%20%3D%20-2)
<span>
Subtract (2n + 3):
</span>
![- (2n + 3) = -2n -3](https://tex.z-dn.net/?f=-%20%282n%20%2B%203%29%20%3D%20-2n%20-3)
<span>
Your equation should now look like this:
</span>
![\frac{1}{2}n - 2 - 3 = 3 - 2n - 3](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B2%7Dn%20-%202%20-%203%20%3D%203%20-%202n%20-%203)
<span>
Combine like terms on both sides:
</span>
![-2 - 3 = -5](https://tex.z-dn.net/?f=-2%20-%203%20%3D%20-5)
![3 - 3 = 0](https://tex.z-dn.net/?f=3%20-%203%20%3D%200)
![\frac{1}{2}n - 5 = -2n](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B2%7Dn%20-%205%20%3D%20-2n)
<span>
Subtract 1/2n from both sides:
</span>
![-5 = -\frac{5}{2}n](https://tex.z-dn.net/?f=-5%20%3D%20-%5Cfrac%7B5%7D%7B2%7Dn)
<span>
Divide both sides by -5/2 to get n by itself:
</span>
![n = 2](https://tex.z-dn.net/?f=n%20%3D%202)
<span>
The value of n is
2.</span>
2n+2(n-4)=56
2n+2n-8=56
4n-8=56
4n=64
n=16
1st side is 16
2nd side is 12
2(-3-7)+5= <span>2(-10)+5= -20 + 5= -15
-15 is your final answer</span>